Formula Development and Characterization Testing of Niacinamide Nano Liposomes as Anti Aging - Dewi, Fitri Jaya Santi Utami; Kuncahyo, Ilham; Saifullah, T.N (PT FORMOSA CENDEKIA GLOBAL, 2024)
Niacinamide has a mechanism of action as an anti-aging agent by increasing fibroblast production by stimulating collagen synthesis and can increase elastin which can prevent wrinkles on the skin of the facial area. The most commonly used method is thin layer hydration followed by sonication. Determination of the optimum formula using expert design with the simplex lattice design method. The purpose of the study was to determine the effect of Phosphatidylcholine concentration of 0.5-5% and Cholesterol concentration of 0.3-5% on the physical properties of niacinamide liposomes, obtain the optimal formula for nano liposomes niacinamide and determine the anti-aging activity of Niacinamide liposomes tested on the backs of rabbits. In the simplex lattice design method, the optimal formula of Phosphotidylcholine with a concentration of 4.7% and cholesterol with a concentration of 0.3% was obtained which produced nanoliposome characteristics including particle size of 135.7 zeta potential -77.19, Adsorption Efficiency of 98.01% and has anti -aging activity with parameters increasing collagen 29.98% and elasticity 65.56%. Niacinamide preparations provide a large increase in anti-aging activity and increase permeability so that they can provide a faster effect than niacinamide serum without liposomes.